Optimizing High School Students' Interest and Motivation in Economics Learning Through the Development of Flashcard Based Augmented Reality Learning Media - Muthmainnah Muthmainnah; Tiara Tiara; Nuriman Nuriman; Muthmainnah Muthmainnah; Tiara Tiara (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The research aims to develop flashcard learning media based Augmented Reality (AR) as an effort to encourage the realization of Sustainable Development Goals (SDGs) point 4 on quality education. The development of AR flashcard learning media is expected to optimize students' interest and motivation in learning economics in the classroom. The development model used in this study is the ADDIE Model. This model includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques used are qualitative and quantitative. Qualitative data comes from observations and interviews related to the analysis of the needs of learning media products to be developed. Quantitative data from questionnaires before and after media implementation. The effectiveness of AR Flashcard Media on student interest and motivation was measured using the Wilcoxon and Mann Whitney Tests because based on the results of the normality test it was known that the data were not normally distributed. The results of the study prove that AR Flashcard Media can optimizing student interest and motivation in economic lesson.